1985
DOI: 10.1079/bjn19850060
|View full text |Cite
|
Sign up to set email alerts
|

The nitrogen requirement of the weanling kitten

Abstract: 1. The nitrogen requirement of the weanling kitten was determined in a series of three experiments. In each experiment, diets were formulated to provide the growing kitten with the essential amino acids at or above the level of requirement. Expt 1 utilized a 4 x 4 balanced Latin square design with two groups of kittens (four male and four female). The crystalline L-amino acid diets were presented at four levels of dietary crude protein (N x 6.25) of 140, 160, 180 and 200 g/kg diet. The design for Expts 2 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Dietary intakes of lysine in adult cats eating a commercial dry expanded diet range from approximately 1 to 3 g/d, with kittens eating approximately half this amount. 33 A dosage of 500 mg given twice daily was chosen as a starting point in cats in our study. Many clinicians prescribe 250 to 500 mg of lysine twice daily for cats with active FHV-1 lesions or for cats prone to recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intakes of lysine in adult cats eating a commercial dry expanded diet range from approximately 1 to 3 g/d, with kittens eating approximately half this amount. 33 A dosage of 500 mg given twice daily was chosen as a starting point in cats in our study. Many clinicians prescribe 250 to 500 mg of lysine twice daily for cats with active FHV-1 lesions or for cats prone to recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while the dietary crude protein (CP, nitrogen × 6.25) requirement of other species such as rats and chicks (NRC, 1978;NRC, 1984) has been well established, the CP requirement of the kitten is not firmly established, particularly when kittens are fed the EAA near the requirement. Different studies have suggested the CP requirement to be anywhere from 160 to 300gCP/kg diet (Anderson et al, 1980;NRC, 1986;Smalley et al, 1985) or possibly even higher (Hammer et al, 1996). Therefore, a series of three experiments was conducted in which kittens were fed diets containing varying levels of CP and EAA at 0.75, 1.0 or 1.5 × the accepted NRC (1986) EAA requirements (EAArq) in order to determine the CP requirement and the range of dietary amino acid patterns that support optimal growth of the kitten.…”
Section: Introductionmentioning
confidence: 98%
“…Different studies have suggested the requirement may range from 160 to 300 g CP/kg diet (Anderson et al, 1980;NRC, 1986;Smalley et al, 1985) or even higher (Hammer et al, 1996). Therefore, three experiments were conducted in which kittens were fed diets containing varying levels of CP and EAA at 2.0 or 3.0 times (×) the NRC (1986) EAA requirements (EAArq), or only EAA, in order to determine the effect of crude protein level and high E:T ratios on growth rates of kittens.…”
Section: Introductionmentioning
confidence: 98%